Relationships between intra-pancreatic fat deposition and lifestyle factors: a cross-sectional study - Mitsushio, Kento; Baden, Megu Y.; Kato, Sarasa; Niki, Akiko; Ozawa, Harutoshi; Motoda, Saori; Ishibashi, Chisaki; Hosokawa, Yoshiya; Fujita, Yukari; Tokunaga, Ayumi; Nammo, Takao; Kozawa, Junji; et al. (Frontiers in Endocrinology, 2023)
Aims The excess deposition of intra-pancreatic fat deposition (IPFD) has been reported to be associated with type 2 diabetes, chronic pancreatitis, and pancreatic ductal adenocarcinoma. In the current study, we aimed to identify a relationship between lifestyle factors and IPFD. Materials and methods 99 patients admitted to the Osaka University Hospital who had undergone abdominal computed tomography were selected. We evaluated the mean computed tomography values of the pancreas and spleen and then calculated IPFD score. Multiple regression analyses were used to assess the associations between IPFD score and lifestyle factors. Results Fast eating speed, late-night eating, and early morning awakening were significantly associated with a high IPFD score after adjusting for age, sex, diabetes status and Body Mass Index (p=0.04, 0.01, 0.01, respectively). Conclusion The current study has elucidated the significant associations of fast eating speed, late-night eating, and early morning awakening with IPFD.